2015
DOI: 10.1039/c4cp05857g
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of photocatalytic and transport properties of TiO2 and ZnO nanostructures for solar-driven water splitting

Abstract: Titanium dioxide (TiO2) and zinc oxide (ZnO) nanostructures have been widely used as photo-catalysts due to their low-cost, high surface area, robustness, abundance and non-toxicity. In this work, four TiO2 and ZnO-based nanostructures, i.e. TiO2 nanoparticles (TiO2 NPs), TiO2 nanotubes (TiO2 NTs), ZnO nanowires (ZnO NWs) and ZnO@TiO2 core-shell structures, specifically prepared with a fixed thickness of about 1.5 μm, are compared for the solar-driven water splitting reaction, under AM1.5G simulated sunlight. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
140
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 257 publications
(144 citation statements)
references
References 52 publications
0
140
0
4
Order By: Relevance
“…However, the major bottle necks such as limited absorption of the visible light and higher recombination of the photo-generated charges are addressed through several strategies including doping, 4 decoration with metal and semiconductor nano-particles 5 and composite formation using other semiconductor materials. 6,7 In recent times, graphene and its derivatives (reduced graphene oxide-rGO) are also being investigated for improving the photo-catalytic/photovoltaic properties by forming composite with TiO 2 . [8][9][10] It is reported that excellent electronic conductivity of this 2D material helps in the separation of photo-generated charges which, in turn, improves the catalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…However, the major bottle necks such as limited absorption of the visible light and higher recombination of the photo-generated charges are addressed through several strategies including doping, 4 decoration with metal and semiconductor nano-particles 5 and composite formation using other semiconductor materials. 6,7 In recent times, graphene and its derivatives (reduced graphene oxide-rGO) are also being investigated for improving the photo-catalytic/photovoltaic properties by forming composite with TiO 2 . [8][9][10] It is reported that excellent electronic conductivity of this 2D material helps in the separation of photo-generated charges which, in turn, improves the catalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Despite possessing higher electron mobility, several studies have shown that ZnO demonstrated a lower photo-conversion efficiency compared to TiO 2 [17,18]. This observation has been attributed to the higher rate of recombination in ZnO compared to TiO 2 [17].…”
Section: Photoexcitation and Charge Separationmentioning
confidence: 83%
“…Proses pembelahan air meliputi tiga tahapan utama; (a) absorpsi foton; (b) pemisahan dan migrasi pembawa muatan yang tereksitasi; dan (c) reaksi permukaan antara pembawa muatan dengan molekul air (2).…”
Section: Pendahuluanunclassified